2021
DOI: 10.3390/w13202843
|View full text |Cite
|
Sign up to set email alerts
|

Determining Stress State of Source Media with Identified Difference between Groundwater Level during Loading and Unloading Induced by Earth Tides

Abstract: The groundwater level might be adopted as a useful tool to explore pre-seismic stress change in the earth crust, because it circulates in the deep crust and should be altered by the processes associated with the preparation of earthquakes. This work makes a new attempt that applies the load/unload response ratio (LURR) technique to study the stress state of the source media before the large earthquakes by calculating the ratio between the water levels during the loading and unloading phases. The change of Coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Then, the LURR value begins to increase above 1.0 gradually from 6 months to 1 year before the occurrence of JZGEQ, reaching the maximum value in 1 to 3 months before the earthquake and subsequently returning to a low level prior to the earthquake. The trend of the LURR time series is similar to that of the previous calculation of LURR using small earthquakes and groundwater level (Yin et al, 2000;Yu et al, 2021), which indicates that the LURR method based on strain observation can better extract the pre-seismic anomalies. On the other hand, under the influence of station distribution, epicentral distance, and observation instruments, there are still noticeable differences between the LURR curves.…”
Section: Application To Strain Datasupporting
confidence: 72%
See 3 more Smart Citations
“…Then, the LURR value begins to increase above 1.0 gradually from 6 months to 1 year before the occurrence of JZGEQ, reaching the maximum value in 1 to 3 months before the earthquake and subsequently returning to a low level prior to the earthquake. The trend of the LURR time series is similar to that of the previous calculation of LURR using small earthquakes and groundwater level (Yin et al, 2000;Yu et al, 2021), which indicates that the LURR method based on strain observation can better extract the pre-seismic anomalies. On the other hand, under the influence of station distribution, epicentral distance, and observation instruments, there are still noticeable differences between the LURR curves.…”
Section: Application To Strain Datasupporting
confidence: 72%
“…et al (2000) used the Benioff strain of small earthquakes as the loading/unloading response in the LURR calculations in different tectonic settings (California, United States, and Kanto region, Japan). Yu et al (2021) proposed a new attempt by using water levels as calculation data and achieved a good application effect. The results of the studies prove that LURR anomalies are relatively significant prior to different earthquakes, that is, the stress accumulation before an earthquake in the seismogenic region will lead to the change of the Benioff strain and water level.…”
Section: The Strain Observation Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, Yu et al 11 have found that the Load/unloading response ratio (LURR) might be applied to explore nonlinear mechanical process associated with earthquake preparation via groundwater level and the pre-seismic changes were explained by dilatancy. This may provide an opportunity for detect pre-seismic electric field changes.…”
Section: Introductionmentioning
confidence: 99%